Digitalization of Accounting: Its Opportunities and Challenges for Professional Accountants in India - Dr. Surendra Kumar Mallick (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Digitalisation of Accounting is a new developing concept with the field of Accounting Profession. Digital accounting converts the paper based accounting to E-accounting. In other words, Digital accounting refers to uses of the latest technology to provide real time accounting, financial information and the optimal data analytics stakeholders need most. Digital accounting is all about saving time, space and money. The present study examines the opportunities, challenges, Professional Accountants Perceptions on digitalisation of Accounting in India. The study evaluates the status quo and progressive trends of digitalisation in accounting profession and how digital accounting system effective in accounting profession.